Ethnicpublicism of Kazakhstan: сomparative studies of the traditions of the Uyghur people of Kazakhstan on the materials of the modern press (Herald of Journalism, 2019)
The Uigurs of Kazakhstan today belong to one of the largest diasporas. Their cultural values as well as the cultural characteristics of other Turkic peoples in a practical sense are the main topic of study. During the period of royal power, world researchers in the person of V.V. Radlov paid  reat attention to Uyghur folklore. During the Soviet era, a large number of studies were carried out related to the different cultural values of the  yghur people. After the collapse of the Soviet power, in order to preserve and exalt the traditional culture, the Uigurs created an independent  press, opened cultural centers and public associations. Today they are an ethnic group developing small and medium businesses in the country.In this regard, the Uyghur people, like other Turkic peoples, made a great contribution to world civilization. Considering such cultural values, it is necessary to emphasize that this topic is one of the pressing problems of our time from the point of view of scientific knowledge. We investigated this problem on the basis of materials published in the Uygur press, through a comparative analysis of other scientific works. Since the materials of the press reflect the culture, character and political and economic place of the people. Scientific research covers the following problems: the resettlement and adaptation of Uigurs in Kazakhstan society, the preservation of family traditions and features of traditional culture, the importance of myths published in the press. In addition to the materials of the press, in a practical sense, sociological studies were carried out; for the purpose of comparative analysis, the scientific works of some authors were used and scientific conclusions were made.
Keywords: Kazakhstan, Uyghur people, traditions, cultural values, traditional culture.